Risk factors for post-polypectomy bleeding; a retrospective case-control study of a high-volume colonoscopy center - Eleftheriadis, Dimitrios; Imalis, Christina; Gerken, Guido; Wedemeyer, Heiner; Duerig, Jan (Zeitschrift für Gastroenterologie, 2021)
Background and aim Post-polypectomy bleeding (PPB) remains an uncommon although serious complication of colonoscopy. The aim of this study is to determine the PPB-prevalence in a secondary care hospital and its associated risk factors.Patients and methods We collected data from 581 patients, with the removal of 1593 polyps between August 2017 and August 2019. A univariate binary logistic regression analysis was conducted retrospectively.Results PPB occurred in only 10 cases, representing 1.7% of patients: immediate in 1.2% and delayed in 0.5%. The number of removed polyps per patient [4.5 (SD 2.59) for hemorrhagic vs. 2.74 (SD 1.98) for non-hemorrhagic group] and the propofol dose [232 mg (SD 93.07) for hemorrhagic vs. 133 mg (SD 57.28) for non-hemorrhagic group] were relevant patient-related risk factors. The polyp-based analysis showed the polyp size [18.4 mm (SD 10.44) for hemorrhagic vs. 4.42 mm (SD 4.29) for non-hemorrhagic group], the morphology [wide-based: OR 24.83 (95 % CI 2.76 – 223.44), pedunculated: OR 56.67 (95 % CI 5.03 – 638.29)], the location at ileocecal valve [OR 20.48, 95 % CI 1.81 – 231.97)], and the polypectomy method [hot snare piecemeal with epinephrine injection: OR 75.38 (95 % CI 7.67 – 741.21)] as significant risk factors for PPB, too.Conclusions The low rate of PPB confirms the safety of the procedure in non-tertiary, high-volume colonoscopy centers. The number of polyps removed per patient, the polyp size, morphology and location, as well as the sedation dose and the method of polypectomy were shown as relevant risk factors.
Keywords: Adenom; Polypektomie; Blutung; Risikofaktor; submukosale Unterspritzung; Adrenalin; Schlinge; Piecemeal-Resektion; Blutstillung; Clip